Film and Domestic Space Architectures, Representations, Dispositif - Baschiera, Stefano 1977-; De Rosa, Miriam 1981- (Edinburgh University Press, 2022)
Brings a range of perspectives, theories and approaches to explore the domestic space in cinemaProvides new methodologies for understanding of the concept of domestic space in cinemaFeatures original case studies of films from different nationalities, periods and genresOffers a new understanding of domestic space as a dispositif and a space for performativityAlthough film and media studies have widely engaged with the different aspects of social space, domestic space in film has rarely been studied in its multiple dimensions. Drawing on a broad range of theoretical disciplines - and with case studies of directors such as Chantal Akerman, Agnès Varda, Claire Denis, Todd Haynes, Amos Gitai, Martin Ritt, John Ford, Ila Bêka and Louise Lemoine - this book goes beyond the representational approach to the analysis of domestic space in cinema, in order to look at it as a dispositif. Adopting this innovative two-fold approach that couples representation and dispositif, the home is studied as an architecture, as the place that embodies, defines and perpetuates the family history, as the milieu of gender and generational struggle, as well as the first site where manifestations of power unfold. All chapters contribute to explore, unpack the complexities and expand on the richness encapsulated in the notion of domesticity and dwelling in its fascinating relation to moving images.ContributorsAnna Backman Rogers, University of GothenburgStefano Baschiera, Queen's University BelfastLukas Brašiškis, New York University Beth Carroll, University of SouthamptonMaud Ceuterick, University of BergenMiriam De Rosa, Coventry UniversityBryan Konefsky, University of New Mexico Adrian Martin, Monash University Nerijus Milerius, Vilnius University Victoria Pastor-González, Regent's University LondonLaura Rascaroli, University College CorkJohn David Rhodes, University of CambridgeMerrill Schleier, University of the PacificIain Robert Smith, King's College, London
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mrz 2022)
Keywords: Film, Media & Cultural Studies; PERFORMING ARTS / Film & Video / Direction & Production; Dwellings in motion pictures